2018
DOI: 10.21276/aimdr.2018.4.4.bc7
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Hormonal Profile (Luteinizing Hormone, Estrogen, Follicle Stimulating Hormone and Prolactin) In the Women Suffering From Acne Vulgaris

Abstract: Background: Acne vulgaris is a pilosebaceous gland disease usually affecting people from puberty to young adulthood due to hormonal changes, but the exact relationship of various hormone to acne is not known. Aims:-The present study has been planned to find out the association of hormonal status with the different grades of acne vulgaris female patients.. Methods: Fifty patients each of Mild (group I), Moderate (group II) and Severe Acne Vulgaris (group III) in age group 15-40 years were included as cases. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In this study, the levels of testosterone in the serum of the cases were significantly lower than the levels in the controls (P < 0.05). Other studies found that female acne vulgaris was significantly associated with elevated serum testosterone [10,16,21]. Each of these studies had a P-value of 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the levels of testosterone in the serum of the cases were significantly lower than the levels in the controls (P < 0.05). Other studies found that female acne vulgaris was significantly associated with elevated serum testosterone [10,16,21]. Each of these studies had a P-value of 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing lipid profiles between the case and control groups, we did not find any statistically significant difference; however, Bakry et There was no substantial correlation between hormone levels and acne severity (P > 0.05). Serum testosterone levels were inversely correlated with DHEAS levels in three studies [14][15][16]. Acne severity was found to be inversely related to the lipid profile [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corticotrophin-releasing hormone (CRH) and cortisol are hormones associated with tension which regulate sebaceous activity [62]. When acne-affected skin is compared to unaffected skin, extremely high levels of CRH expression are detected in the sebaceous glands [63].…”
Section: Corticotrophin-releasing Hormone (Crh) and Cortisolmentioning
confidence: 99%